2012
DOI: 10.2503/jjshs1.81.150
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Expressed Proteins in the Different Stages of the Style Development of Self-incompatible ‘Hyuganatsu’ (Citrus tamurana hort. ex Tanaka)

Abstract: In Citrus, self-incompatibility (SI) regulation is gametophytic, and this phenomenon is an economically critical problem for some Citrus cultivars without high parthenocarpic ability. Few molecular biological studies of SI in Citrus have been performed, and the molecular mechanism of SI has not been clarified. To investigate the effect of different stages of style development on pollen tube behavior, flower buds of self-incompatible 'Hyuganatsu' (Citrus tamurana hort. ex Tanaka) were histologically assayed. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Some studies have reported the inhibition of self-pollen tubes found in the ovary (Ye et al, 2009). The inhibition of pollen tube growth has been observed in different locations in 'Hyuganatsu'-in the stigma (Yamashita, 1978), in the center of the style (Uchida et al, 2012), and at the bor-der between the stigma and style (Honsho et al, 2012). Some practical methods to break SI have been reported.…”
Section: General Features Of Citrus Self-incompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported the inhibition of self-pollen tubes found in the ovary (Ye et al, 2009). The inhibition of pollen tube growth has been observed in different locations in 'Hyuganatsu'-in the stigma (Yamashita, 1978), in the center of the style (Uchida et al, 2012), and at the bor-der between the stigma and style (Honsho et al, 2012). Some practical methods to break SI have been reported.…”
Section: General Features Of Citrus Self-incompatibilitymentioning
confidence: 99%
“…RNAseq was used for comparing no-, self-, and cross-pollination in the stigmas and styles of self-incompatible 'Xiangshui' lemon (Zhang et al, 2015). In 'Hyuganatsu', protein expression between different stages at 1-, 3-, and 5-day before anthesis was compared using 2D polyacrylamide gel electrophoresis (PAGE) and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (Uchida et al, 2012).…”
Section: Female Determinant Of Citrus Self-incompatibility Is the S-r...mentioning
confidence: 99%
“…The first eight all participated in different biological processes while the last PG may be related to the SI reaction. The comparative studies in proteomics may be helpful in isolating the key proteins related to SI and eventually in explaining the reproduction process [ 76 ]. These studies uncover the special proteins in SC and/or SI process by proteomic approaches, which may also expand our insights on the possible pathways related to the interactions during both compatible and incompatible pollination.…”
Section: Proteomic Analysis Of Pollen-pistil Interaction In Si Resmentioning
confidence: 99%
“…Hyuganatsu occupies an important position as a late-season citrus cultivar in the fruit industry of Miyazaki prefecture. Hyuganatsu substantially has neither parthenocarpic traits nor self-compatibility (Miwa, 1951), for which approaches to genetic and molecular bases have recently begun Ngo et al, 2011;Uchida et al, 2012). As a result of these characteristics, a pollinizer is required to set the fruits, which ultimately contain many seeds (Yamamoto et al, 1995).…”
Section: Introductionmentioning
confidence: 99%